Influence of plasma nitriding on surface layer of M50NiL steel for bearing applications - Reddy C. Anil Kumar; Rao Pothamsetty Kasi V.; Venkatesh Begori; Rao Boggarapu Nageswara (Journal of the Mechanical Behavior of Materials)
Research on plasma nitriding was carried out on M50NiL bearing steel, subject to temperatures ranging from 460 to 560°C over periods from 4 to 40 h, while keeping the gas mixture at a steady ratio of 80H2:20N2. To examine the phase structure and chemical composition of the plasma nitrided layer, techniques such as energy dispersive spectrometry (EDS) and X-ray diffraction (XRD) were utilized. The M50NiL steel sample heated to 550°C for 24 h was found to contain an unusually high amount of nitrogen, as per the EDS analysis. The majority of the nitrided layer’s composition is made up of nitrogen-expended phases. Following XRD analysis, several peaks were identified, including α′-FeN, γ′-FeN, γ′-Fe3N, α′-Fe, and γ′-Fe. The main objective of this research was to explore the impact of temperature on the microstructure, hardness, wear resistance, and corrosion resistance of the surface nitrided layers. The steel that underwent nitriding at 500°C for 4 h demonstrated a significantly higher surface hardness of 1,332 HV, with an additional increase in case depth by 62.00 μm. The findings suggest that both the duration and temperature of nitriding affect the depth of the plasma nitrided layer. The surface hardness of the plasma samples was found to be notably improved. The steel sample, PN 500, nitrided at 08 h, exhibited the highest wear resistance among the nitride samples. The wear resistance of the samples was shown to be significantly enhanced. Potentiodynamic tests were conducted to assess the corrosion resistance of the nitrided steel, revealing that it was notably more resistant than the untreated steel. Furthermore, it was observed that steel nitrided for shorter durations at lower temperatures (e.g., 460°C for 4 h) demonstrated superior corrosion resistance compared to samples nitrided at higher temperatures.